Synthesis of Gossipy Products of Pyrimidine Bases and Getting Their Water-Solved Complexes - Khakberdiev Shukhrat Mahramovich; Karimova Feruza Sattarovna; Mamatova Farangiz (Genius Publishing Group, 2022)
Gossypol itself and its derivatives are currently used in medical practice as a means against viral diseases, as they have a wide range of physiological activity. Schiff bases with heterocyclic amino compounds of gossypol, and water-soluble supramolecular complexes were obtained and their structure was studied using the IR, -UB, and -PMR spectra.
Keywords: Gossypol; 2-aminopyrimidine; 2-amino-4; 4,6-dimethyl pyrimidine